Visiting Professorships. - Kiger, Jack E.; Warren, Carl S. (The Accounting Review, 1975)
Abstract Visiting professors are becoming a common phenomenon in the academic world, as of April 1975. Visiting professor arrangements involve faculty members taking leaves of absence from their home institutions and correspondingly obtaining temporary appointments, which normally do not extend beyond one academic year, at other institutions. The objective of this article is to investigate the nature of visiting professorships from the point of view of both the participating faculty member and the sponsoring institution. In addition, potential benefits accruing to the academic community as a whole, as well as the question of whether the American Accounting Association should encourage visiting professorships, are explored. A questionnaire was developed and sent to 300 faculty members randomly selected from the 1973 American Accounting Association membership directory. The article also presents information about the extent to which visiting professorships currently exist. The faculty questionnaire results indicated that 22% of the respondents had been involved, at some time during their academic careers, in a visiting faculty arrangement. Another 10% of the respondents had considered and rejected such an offer. Approximately 32% of the faculty members surveyed had, at one time, decided either to accept or reject a visiting professorship.